Utilization of Coconut Pulp as Methane Inhibitor Feed on Meat Quality of Goat - Erwin Hubert Barton Sondakh; Jerry Audy Donny Kalele; Friets Semuel Ratulangi; Conny Palar; Siane Rimbing (Faculty of Animal Science, Jenderal Soedirman University in associate with Animal Scientist Society of Indonesia (ISPI), 2022)
This research was conducted to know the impact of methane reduction in ruminants using coconut pulp as feed substrate on the quality of goat meat. This study used coconut pulp as an antimetanogenic substrate and was added to ruminant feed. There were twenty goats aged + 1 year. The feed was given with a formulation of 60: 40% forage and concentrate in dry matter with a composition according to the needs of the goats. This research was carried out by treating coconut pulp with four levels of different treatment, namely 5, 10, 15, and 20% and compared with the treatment without using coconut pulp (0%). This experiment used a completely randomized design with four replications. The average difference of treatment was continued with the Duncan Multi Range Test (DMRT) test. The goats were kept for 60 days and they were slaughtered to measure the quality of meat. The variables measured were physical and chemical quality of goat meat. The results showed that the physical quality and the chemical quality of the meat had no significant effect. The conclusion of this research is the use of coconut pulp as an antimethanogenic substrate for goat feed can maintain the physical and chemical quality of meat and reduce meat cholesterol.